2018
DOI: 10.1002/syn.22025
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a 3xTg‐AD mouse model of Alzheimer's disease with the senescence accelerated mouse prone 8 (SAMP8) background

Abstract: No model fully recapitulates the neuropathology of Alzheimer's disease (AD). Although the triple-transgenic mouse model of AD (3xTg-AD) expresses Aβ plaques and tau-laden neurofibrillary tangles, as well as synaptic and behavioral deficits, it does not display frank neuronal loss. Because old age is the most important risk factor in AD, senescence-related interactions might be lacking to truly establish an AD-like environment. To investigate this hypothesis, we bred the 3xTg-AD mouse with the senescence-accele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 107 publications
(162 reference statements)
0
10
0
Order By: Relevance
“…Indeed, decreased NLGN1 was found at 4 months, an age at which cognitive symptoms are just starting to manifest and have been attributed to intraneuronal Aβ 57 . This model generally shows signs of neuronal death, human Aβ precursor protein (hAPP) deregulation, and Tau pathology later in life 42,60,61 , but these may all contribute to NLGN1 decrease together with alterations in Preselinin-1 in this model. The observation that only the females show this early decrease likely resides in the worst pathology observed in 3xTg-AD females in comparison to 3xTg-AD males.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Indeed, decreased NLGN1 was found at 4 months, an age at which cognitive symptoms are just starting to manifest and have been attributed to intraneuronal Aβ 57 . This model generally shows signs of neuronal death, human Aβ precursor protein (hAPP) deregulation, and Tau pathology later in life 42,60,61 , but these may all contribute to NLGN1 decrease together with alterations in Preselinin-1 in this model. The observation that only the females show this early decrease likely resides in the worst pathology observed in 3xTg-AD females in comparison to 3xTg-AD males.…”
Section: Discussionmentioning
confidence: 90%
“…The observation that only the females show this early decrease likely resides in the worst pathology observed in 3xTg-AD females in comparison to 3xTg-AD males. Indeed, 3xTg-AD females have repeatedly been reported to have, in particular, higher hAPP and Aβ levels than males 60,62,63 . Alternatively, a compensatory mechanism linked to the encoding of other NLGNs by sex chromosomes 64,65 , could also contribute to the sex-dependent decrease in NLGN1.…”
Section: Discussionmentioning
confidence: 99%
“…An accumulating number of studies have suggested that cell senescence exerts a dominant role in a wide variety of diseases, including hepatocarcinogenesis (32), intervertebral disc degeneration (33), diabetic nephropathy (34), diabetic cardiomyopathy (35), Parkinson's disease (36) and Alzheimer's disease (37). Additionally, the crucial role of cell senescence in the development of osteoporosis has also been widely recognized (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…The Morris Water Maze has been used more often than the Barnes Maze, which we utilized because it is less stressful (Barnes, 1979;Gawel et al, 2019;Hunsberger et al, 2014;Illouzm et al, 2016;Paul et al, 2009;Rosenfeld and Ferguson, 2014;Stover et al, 2015;Suzuki and Imayoshi, 2017;Varodayan et al, 2018). Using the Barnes Maze to compare nontransgenic and 3xTG-H mice at various ages, some studies revealed deficits in age-matched 3xTG-H mice (Fertan et al, 2019;Vandal et al, 2014), while others showed no consistent differences by genotype (Stover et al, 2015;Virgili et al, 2018). Comparing 3xTG-H mice with C57 controls, Aloni et al reported no difference in Barnes Maze performance (Aloni et al, 2019), in agreement with our results for naïve mice (Fig.…”
Section: Spatial Memory Acquisitionmentioning
confidence: 99%